The Influence of Resource Based View and Motivation on The Performance of Grilled Chicken UMKM - Syahyono, Syahyono; Fajarwati, Kharisma; Khumairoh, Hasna; Dirgantara, Haikal Restu; Putra, Aga Victoria (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Micro, small, and medium enterprises (MSMEs) play a significant role in the Indonesian economy, especially in terms of revenue sharing and job creation. This study was conducted to determine how resource-based perspective (RBV) and motivation affect business performance in micro, small, and medium enterprises (MSMEs) in the grilled chicken culinary sector in Rawalumbu District, Bekasi City. The results of the analysis show that RBV significantly affects motivation and business performance, but motivation does not significantly affect business performance. Primary data were collected through quantitative methods. This study shows that the main strategy for competitive MSMEs is optimizing internal resources. This study provides insight to MSME actors on how to manage resources and increase motivation to improve their competitive advantage.